AB1081-HPR Pharmacological Adherence To Conventional or Biological Therapy in Patients with Rheumatoid Arthritis in A Colombian Specialized Rheumatology Center. (15th July 2016) - Palacio, N.; Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Castro, C.; et al.
Abstract : Background: The lack of pharmacological adherence and consecutive therapeutic failure is a prevalent and relevant problem in clinical practice, especially in the treatment of chronic diseases such as rheumatoid arthritis (RA). In the context of chronic diseases, World Health Organization considers lack of adherence like a public health priority because represents negative consequences like: therapy failures, higher rates of hospitalization and increased costs of health care. Objectives: The aim of this observational study was determine adherence to treatment in patients with RA, their demographic characteristics and clinical variables. Methods: An observational, descriptive cross sectional study conducted in a non-probability sample of convenience in patients with RA who consult to rheumatology institution specialized in RA patients. Descriptive epidemiology was applied for continuous variables, measures of central tendency and dispersion for categorical and qualitative variables (averages/percentages); we used Pearson's chi-squared test (χ 2 ) and T student test to evaluate bivariate correlation. Results: 356 patients were included, 186 (52%) received DMARDs therapy and 170 (48%) biological therapy. 309 (86%) were female and 47 (43%) were male meanDAS28 was 2.5 ± 1 HAQ was 0.87 ± 1.3. The most frequent comorbidity was osteoporosis 145 (40%) and hypertension 135 (37%). 103 (28%) participants suspended the medication when they felt polimedicated. In the group using DMARDs 71 (38%) suspended the medication due to an adverse event and in the biological therapy group 55 (32%). 71 (38%) patients in the group with DMARDs referred administrative difficulties while in the group with biological therapy 56 (32%) referred the same issue. When we explored the adherence, regarding age the group where we found fewer adherence in the group between 40 and 60 years this correlation was not statistically significative. When patients suspended the medication when they felt medicated with many drugs mean DAS28–2.6 higher than who did not suspend medication mean DAS28–2.4. When the medication due to an adverse event was suspended mean DAS28–2.57 higher than those who did not suspend the medication (DAS28–2.46) and was statistically significative. Conclusions: This study shows that most of patients (two thirds) are adherent to conventional or biological treatment; however a important number remains non-adherent with a higher DAS28 score with clinical and economical implications. Disclosure of Interest: None declared